Surgical and oncological results after rectal resections with or without previous treatment for prostate cancer - Tomminen, T.; Huhtala, H.; Kotaluoto, S.; Veitonmäki, T.; Wirta, E.-V.; Hyöty, M. (Frontiers in Surgery, 2024)
Introduction: Previous prostate cancer (PC) treatment may affect the surgical and oncological results of later rectal cancer surgery, but there are only few studies about this special group. Here we present 3-year surgical and oncological results of rectal cancer patients with previous treatment for PC from a single Finnish tertiary referral centre. Material and methods: Information of all male rectal cancer patients treated during 1997-2016 in Tampere University Hospital (TAUH) were gathered from medical records. Altogether this study included 553 rectal cancer patients operated with curative intention and 54 of those (9.8%) had history of previous treatment for prostate cancer. Results: Patients in PC group were older and had more comorbidities compared to non-PC group. PC patients had a significantly higher risk for permanent stoma compared to non-PC patients, 61.5% vs.45.2%, respectively, p=0.025. PC patients seemed to have more lower tumours than non-PC patients (87% vs. 75%, respectively, p=0.05). Overall, 3-year survival (OS) for PC and non-PC patients was 74.1% vs 80.6%, no significant difference between study groups even in age adjusted comparison, [Hazard ratio (HR) 1.07, confidence interval (CI) 95% 0.60-1.89]. In univariable analysis, radically operated patients without history of PC had improved overall survival (OS), (HR 2.46,, P=0.004. Still, only higher age adjusted Charlson comorbidity index (CCI) and low tumour location (<10cm) had independent prognostic impact for worse OS in multivariable analysis (HR 1.57, 95%, p<0.001 and HR 2.74, p=0.007, respectively). There were no differences between groups in disease-free nor local recurrence-free survival.Rectal cancer in patients with previous treatment for prostate cancer is located more frequently in mid or low rectum and have increased risk for permanent stoma. In radically operated rectal cancer, PC group had worse OS in univariable analysis. However, the only independent prognostic factors for worse OS to stand out in multivariable analysis included higher CCI and low tumour location.